Pemanfaatan Taman Kota Lumintang Sebagai Aktifitas Leisure And Recreation Bagi Remaja Kota Denpasar - Suriyadi, Thalia Natinska; Suryasih, Ida Ayu (JURNAL DESTINASI PARIWISATA, 2018)
The youth are known to have various activities in their daily lives . a lot of them needed the time to clear their mind from the stress. Many teenagers visit the Lumintang City Park during their spare time to recharge and reinvigorate their energy with various recreational activities . The main purpose of conducting this study is to ascertain the utilization of Lumintang City Park and the significance of recreation obtained by the youth following their recreational activities at Lumintang City Park. Data were collected through observation and questionnaire, and to determine sample using the quota sample to the tune of 50 respondents . The result of the conducted study had shown that Lumintang City Park is utilized by the youth as a place to exercise, lounge around, enjoy the evening atmosphere, cure boredom, and many other activities, with a relatively dominating advantage specifically in the utilization of Lumintang City Park as a place to exercise. Moreover, the significance of the recreation obtained by the youth in the wake of their activities at Lumintang City Park is dominated by recreation and well-being. Keywords: : city park, leisure and recreation, youth